The Effect of Leader Humor on Subordinates’ Working Status: A Meta-Analysis (Asian Business Research, 2022)
Leader humor in workplace can change the working state of subordinates. However, existing empirical studieshave failed to determine whether the effect of positive and negative leader humor on the working status ofsubordinates is normal, or whether the effect of leader humor in profit and non-profit organizations or underEastern and Western culture background is also different. To answer these questions, literature on therelationship between Leader humor and subordinate working status from 2009 to 2020 was searched, and 56effect values of positive leader humor (a total of 16544 samples) and 24 effect values of negative leader humor(a total of 7781 samples) were obtained. The results of meta-analysis show that: (1)There is a significant positiverelationship between positive leader humor and subordinates’ work status, while there is a significant negativerelationship between negative leader humor and subordinates’ work status; (2) Positive leader humor promotesthe subordinates’ behavior state improving by ameliorating their positive psychological state or attitude state inthe workplace; (3)Negative leader humor inhibits the subordinates’ behavior state improving by incurring theirnegative psychological state or attitude state in the workplace.